Urbach”™s tail in indirect band-gap semiconductors - Durán Flores, Larissa; Fonthal, Gerardo (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> In this work, the band tail parameters in GaP, Ge and Si, indirect band gap semiconductors, have been studied using the published data. It is established that the optical absorption edge in these materials obeys Urbach”™s Rule. It is also found that the structural disorder in monocrystalline materials is around zero, due to the natural disorder of the crystal lattice. The width of the exponential tail or Urbach”™s energy is found between 20 and 39meV at 77K and 60-70meV at 300K. Also, the steepness parameter s is above 0.55, indicating a strong phonon interaction typical in indirect band gap semiconductors.